2021
DOI: 10.1371/journal.pone.0259092
|View full text |Cite
|
Sign up to set email alerts
|

Impact of staffing model conversion from a mandatory critical care consultation model to a closed unit model in the medical intensive care unit

Abstract: Background The intensive care unit (ICU) staffing model affects clinical outcomes of critically ill patients. However, the benefits of a closed unit model have not been extensively compared to those of a mandatory critical care consultation model. Methods This retrospective before-after study included patients admitted to the medical ICU. Anthropometric data, admission reason, Acute Physiology and Chronic Health Evaluation II score, Eastern Cooperative Oncology Group grade, survival status, length of stay (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To our knowledge, our study is the first in Korea to explore the effects of the CSICU system. We found that the CSICU system led by intensivists exerts a positive impact on patients' prognosis and ICU operation [10][11][12][13][14][15]. This study chronologically investigated the effect of the application of the CSICU system on the clinical outcome of only surgical patients to confirm its usefulness in the surgical ICU.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, our study is the first in Korea to explore the effects of the CSICU system. We found that the CSICU system led by intensivists exerts a positive impact on patients' prognosis and ICU operation [10][11][12][13][14][15]. This study chronologically investigated the effect of the application of the CSICU system on the clinical outcome of only surgical patients to confirm its usefulness in the surgical ICU.…”
Section: Discussionmentioning
confidence: 91%
“…Intensivists are advantageous for the management of critically ill patients due to their high understanding of the pathophysiology of critically ill patients, evidence-based management, use of systematic treatment protocols, and high proficiency in high-level treatments such as CRRT and mechanical ventilation. Therefore, there are several reports that the closed ICU system in which the intensivist completely manages critically ill patients improves the clinical outcome of these patients [10][11][12][13][14][15]. However, despite these positive reports, a truly closed ICU system, which is managed by the ICU staff composed of intensivists, has not been widely established around the world.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the primary care physician, such as a surgeon, internal medicine doctor, or family doctor, retains overall responsibility for the patient admitted to the ICU. Scientific evidence indicates that closed units may yield better survival rates than open ones [ 7 , 8 ]. However, in South Africa, only 7% of public units and less than 1% of private units were reported to be “ideal closed units” in 2007 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%